Critical market shares for investors and access seekers and competitive models in fibre networks - Stephan Jay; Karl-Heinz Neumann; Thomas Plückebaum (International Telecommunications Society (ITS), 2011)
In this paper we consider and evaluate NGA architectures which meet the foreseeable future bandwidth demand and allow for highest bandwidth and quality for end-users and which no longer rely on copper cable elements. These are FTTH architectures only. From all available FTTH architectures we concentrate on the two most relevant architectures in Europe, Ethernet Point-to-Point and GPON. We assume the incumbent to be the investor in the NGA network infrastructure. If the NGA architecture is based on a Point-to-Point fibre plant we have modelled the competitors as using unbundled fibre loops as the wholesale access service. If the architecture is based on a Point-to-Multipoint fibre plant, we consider an active wholesale access (bitstream access) at the MPoP or at the core network node locations. Our basic modelling relies upon an engineering bottom-up cost modelling approach. We model the total cost of the services considered under efficient conditions, taking into account the cost of all network elements needed to produce these services in the specific architecture deployed. This approach is coherent with a Long Run Incremental Cost approach as applied in regulatory economics. Our modelling approach generates a broad set of results including the relative performance of the various network architectures, investment requirements and the degree of profitable coverage. In this paper, however, we focus on the results on the potential for competition and potential market structures in an NGA environment.
Keywords: L10; L13; L14; 330; NGA architecture; cost modelling; FTTH; coverage; access models; unbundling